The Battles of Al-Fallujah: Urban Warfare and the Growth of Air Power - Head, William (Air power history, 2013)
First Marine Expeditionary Force (I MEF) operations officer, declared that weapon precision was unprecedented. While tactical roles such as close air support (CAS) and vehicular attacks increased over time even this was often more cheaply executed by helicopter gunships using "hell-fire" missiles, than fixed-wing aircraft using 500-pound bombs.